2013
DOI: 10.1186/1471-244x-13-64
|View full text |Cite
|
Sign up to set email alerts
|

Expectations, experiences and attitudes of patients and primary care health professionals regarding online psychotherapeutic interventions for depression: protocol for a qualitative study

Abstract: BackgroundIn the year 2020, depression will cause the second highest amount of disability worldwide. One quarter of the population will suffer from depression symptoms at some point in their lives. Mental health services in Western countries are overburdened. Therefore, cost-effective interventions that do not involve mental health services, such as online psychotherapy programs, have been proposed. These programs demonstrate satisfactory outcomes, but the completion rate for patients is low. Health profession… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 28 publications
1
10
0
2
Order By: Relevance
“…For example, in studies of computer based and self-directed approaches for depression, providers’ attitudes were more negative than the attitudes of patients themselves (Montero-Marin et al 2013; Whitfield and Williams 2004). Such attitudes are important and warrant additional attention.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in studies of computer based and self-directed approaches for depression, providers’ attitudes were more negative than the attitudes of patients themselves (Montero-Marin et al 2013; Whitfield and Williams 2004). Such attitudes are important and warrant additional attention.…”
Section: Discussionmentioning
confidence: 99%
“…Adults presenting with depressive symptoms in PC were randomized to receive either iTAU from their GP or an Internet-based intervention program (Smiling is Fun) for depression, in this case, either with psychotherapist support (LITG) or without it (CSG). The trial protocol of the study [ 16 ], the manual used to implement the program [ 17 ], and a study on expectations of depressed PC patients have already been published [ 18 , 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…This methodological triangulation was able to increase consistency and rigor by combining multiple techniques, maximizing the breadth and depth of perspectives. The complete details of the study protocol are reported elsewhere [ 57 ].…”
Section: Methodsmentioning
confidence: 99%